Research status and hotspots of social frailty in older adults: a bibliometric analysis from 2003 to 2022 - Wang, Hengxu; Chen, Xi; Zheng, MingXiang; Wu, Ying; Liu, Lihua (Frontiers in Aging Neuroscience, 2024)
Background Social Frailty is a significant public health concern affecting the elderly, particularly with the global population aging rapidly. Older adults with social frailty are at significantly higher risk of adverse outcomes such as disability, cognitive impairment, depression, and even death. In recent years, there have been more and more studies on social frailty, but no bibliometrics has been used to analyze and understand the general situation in this field. Therefore, by using CiteSpace, VOSviewer, and Bilioshiny software programs, this study aims to analyze the general situation of the research on social frailties of the older adults and determine the research trends and hot spots. Methods A bibliometric analysis was conducted by searching relevant literature on the social frailty of the older adults from 2003 to 2022 in the Web of Science core database, using visualization software to map publication volume, country and author cooperation networks, keyword co-occurrences, and word emergence. Results We analyzed 415 articles from 2003 to 2022. Brazil has the highest number of articles in the field of social frailty of the older adults, and the United States has the highest number of cooperative publications. Andrew MK, from Canada, is the most published and co-cited author, with primary research interests in geriatric assessment, epidemiology, and public health. “Social Vulnerability,” “Health,” “Frailty,” “Mortality,” and “Older Adult” are among the research hotspots in this field. “Dementia,” “Alzheimer’s disease,” “Population,” and “Covid-19” are emerging research trends in social frailty among the older adults. Conclusion This scientometric study maps the research hotspots and trends for the past 20 years in social frailty among the older adults. Our findings will enable researchers to better understand trends in this field and find suitable directions and partners for future research.